(untitled) (Research, Society and Development, 2021)
The article intended to answer the following question: Does the use of a didactic sequence that makes use of building applications improve the teaching and learning of the polynomial function of the 2nd degree? In order to analyze the construction of applications, from block programming, in App Inventor, in a didactic sequence, for the understanding and solving of problems involving 2nd Degree Polynomial function. The locus of the research was in a public school in the city of São João de Pirabas-PA, Brazil. The subjects were 40 students from the 1st year of high school. Data were obtained from written records and audio recordings to be analyzed according to Durval’s theories of microgenetic and semiotic analysis. The methodology used in the preparation of the activities was Mathematical Modeling and the research methodology Didactic Engineering. The proposed didactic sequence presents three activities aimed at teaching polynomial functions in high school. As a result of the research, we observed, from the application of the didactic sequence, that the students were more enthusiastic about learning the subject studied, in addition to reaching an understanding of the subjects more quickly, in a collaborative and participatory environment, in which progress was seen. in the autonomy of these, resulting in better performance in the resolution of the issues.